Pengaruh Rasio Keuangan terhadap Harga Saham - Ardins Kristiani Selfhana Hendrik (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to determine the financial ratios that affect stock prices. The population in this study are all companies listed in Indonesia according to the OSIRIS Database. The research sample was selected using purposive sampling technique so that a total sample of 51 food and beverage companies listed on the OSIRIS Database in 2019-2021 was obtained. The independent variables in this study are ROA, NPM, CR, QR, and EPS, while the dependent variable is stock price. The data analysis technique for hypothesis testing uses multiple linear regression analysis. The results showed that Return on Asset, Net Profit Margin, Current Ratio, and Quick Ratio have no significant effect on the company's stock price, while Earning Per Share has a significant effect on the company's stock price. This study contributes to enriching companies with information about factors that affect stock prices that investors tend to pay attention to, and as a contribution to the application of signaling theory in the development of science, especially those related to financial statement analysis